2023
DOI: 10.3390/bs13060483
|View full text |Cite
|
Sign up to set email alerts
|

Creative Performance and Conflict through the Lens of Humble Leadership: Testing a Moderated Mediation Model

Abstract: This study developed and tested a moderated mediation model by examining the relationships between humble leadership (HL), emotional intelligence, employee conflict (EC), and creative performance (CP), using resource-based theory as the theoretical foundation. We conducted a cross-sectional survey of 322 employees and their immediate supervisors (n = 53) from the telecom sector in Pakistan. The data was analyzed using AMOS 21 and SPSS 26. The results demonstrate that HL has a positive effect on creative perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
(120 reference statements)
0
0
0
Order By: Relevance
“…This is mainly because a humble leader gives value and respect to his/her followers; consequently they show greater work engagement. Further, humble leaders play a vital role in building a safe working environment that promotes maximum performance and engagement (Walters and Diab, 2016;Liu et al, 2023). Compared with other leadership styles, humble leaders tend to be more helpful and supportive toward their followers, thus increasing their dedication, absorption, and vigor.…”
Section: Humble Leadership and Work Engagementmentioning
confidence: 99%
See 4 more Smart Citations
“…This is mainly because a humble leader gives value and respect to his/her followers; consequently they show greater work engagement. Further, humble leaders play a vital role in building a safe working environment that promotes maximum performance and engagement (Walters and Diab, 2016;Liu et al, 2023). Compared with other leadership styles, humble leaders tend to be more helpful and supportive toward their followers, thus increasing their dedication, absorption, and vigor.…”
Section: Humble Leadership and Work Engagementmentioning
confidence: 99%
“…Recent conceptualizations highlight dimensions including self-awareness, appreciation of others, and a commitment to creating a collaborative and inclusive work environment (Ou et al, 2014). Empirical studies by Liu et al (2023) and Wang et al (2018) identified key dimensions, including openness to admitting mistakes, valuing others' strengths, a willingness to learn, and a focus on collective success. Creativity on the other hand is defined as the process of idea exploration, generation, championing, and implementation (Scott and Bruce, 1994;Carmeli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations